ANALISIS SEMIOTIK MASALAH ETIKA DALAM IKLAN (STUDI KASUS IKLAN MAJALAH “AYAHBUNDA” TAHUN 2013 DAN TAHUN 2014) - Lucy Max (Master of Communication Science Program, Universitas Diponegoro, 2018)
By doing an analysis on the word and picture choices in the advertisement of AC Sharp in th “ayahbunda” Magazine of 26th Edition, December 24, 2012 – Januari 6, 2013, page 3 and in the Dettol Liqiut Soap of the same magazine 20th Edition, October 6 – 9, 2014, it was found that there is a potential problem of ethics in the advertisements. The creative execution of advertisements leaves behind a gap between rationality and creativity when one tries to demonstrate the quality of products. The ideal things is that the decision concerning “end and means” can be accounted for as far as the decisions does not produce misrepresentation, false images, exaggerated expectation, unwarranted expending of money and getting something that does not live up to promises.